Examining Antecedents of Job Stress: A Demographic Analysis of State Bank of India Employees working in Cachar District of Assam - Barman , Nitashree (Gyan Management Journal, 2023)
The present study aims at assessing antecedents of job stress among employees of State Bank of India (SBI) operating in the Cachar district of Assam, taking into account gender, designation, and job experience. The findings reveal that male bank employees experience more job related stress than their female counterparts. Furthermore, employees in managerial positions exhibit higher stress levels than clerks, primarily due to role overload and poor relationships with other staff. Regarding job experience, the results indicate that employees with less than five years of experience endure a significant amount of stress, particularly related to role ambiguity, role conflict, group politics, and unfavorable working conditions.